Toward Customizable Smart Gels: A Comprehensive Review of Innovative Printing Techniques and Applications - Rizwan Ul Hassan; Naseem Abbas; Jongkuk Ko (Gels)
New production technologies have transformed modern engineering fields, including electronics, mechanics, robotics, and biomedicine. These advancements have led to the creation of smart materials such as alloys, polymers, and gels that respond to various stimuli. This review focuses on smart materials (SMs), including their variety and fabrication techniques, that can be used to construct three- or four-dimensional structures. The mechanisms and designs of smart materials, limitations of current printing technologies, and perspectives for their future uses are also discussed in this review. The printed smart materials are expected to have a major impact on the design of real-world applications.